Live, Love, Lead - Houston, Brian ([Sydney] : HarperCollins, 2015)
What would happen if one of Christianity's most respected leaders shared everything he has learned about finding God in life's difficulties and living an extraordinary life? Brian Houston has done just that in his international bestseller LIVE LOVE LEAD. When Global Founder and Senior Pastor of Hillsong Church, Brian Houston, set out to pioneer with 45 people and a school hall in the suburbs of Sydney, Australia, he was unsure of the highs and lows, sacrifices and disappointments that would mark the 32-year journey of miraculous opportunities and dreams come true. LIVE, LOVE, LEAD is his story, woven in to the greatest story ever told, with room for chapters all your own to be written and re-written. It's a collection of tried and proven principles based on powerful biblical truths and life tested experiences that will enable you to unlock your personal vision, find God in your difficulties and discover what it means to live with eternity in mind. This book is for those who are intrigued by Brian and Hillsong Church - an Australian story with global impact - and for seasoned believers and spiritual seekers alike, longing to uncover the secret to living a more fulfilling life.
Imprint: HarperCollins.
Adult.
Print version record
Keywords: Religion: general; Religion - General; Christian life; Christian life; Success -- Religious aspects -- Christianity; Australian; Electronic books; Religion & Spirituality